Multistate Degradation Model for Prognostics of Solder Joints Under Vibration Conditions. Issue 4 (1st July 2016) - Tang, Wei; Jing, Bo; Huang, Yifeng; Sheng, Zengjin; Jiao, Xiaoxuan
Abstract : This paper develops a multistate degradation structure of the solder joints which can be used under various vibration conditions based on nonhomogeneous continuous‐time hidden semi‐Markov process. The parameters of the structure were estimated to illustrate the stochastic relationship between the degradation process and the monitoring indicator by using unsupervised learning methods. Random vibration tests on solder joints with different levels of power spectral density and fixed forms were conducted with a real time monitoring electrical resistance to examine the suitability of the model. It was experimentally verified that the multistate degradation structure matches the experimental process reasonably and accurately. Based on this multistate degradation model, the online prognostics of solder joint were analyzed and the results indicated that faults or failures can be detected timely, leading to appreciate maintenance actions scheduled to avoid catastrophic failures of electronics.